A Primer on Librarians Sabbaticals: A Case Study of a Six-Month Sabbatical at Home and Abroad. (2nd October 2018) - Kraus, Peter L.
ABSTRACT: Sabbaticals have long been part of the research culture in American higher education and academic libraries. A review of the scholarly literature shows that sabbaticals serve a number of purposes for librarians. By providing time for reviewing best practices at other libraries, working at other libraries within and outside the United States, or pursuing post-graduate degrees, sabbaticals have allowed those in academic libraries to improve their skill sets and knowledge base to improve themselves and their libraries. A successful sabbatical takes planning and focus; the author of the article will use his sabbatical, which took place between July and December 2015 in Salt Lake City, Utah, and St. Stephen's House, an Anglican Theological College and Permanent Private Hall at Oxford University, as model for this primer on having a successful sabbatical.